2022
DOI: 10.3390/su14159613
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Efficiency of Transport Infrastructure Connectivity and Trade

Abstract: Analyzing the efficiency of transport infrastructure connectivity and trade in the Regional Comprehensive Economic Partnership (RCEP) is very important for regional integration for international trade in the RCEP. This study aims to significantly measure the efficiency of the connectivity of infrastructure in the RCEP for improving the performance of infrastructure connection and suggest the way to improve the connection of infrastructure. Therefore, the input and output variables of infrastructure connectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…• Efficiency. Well-designed infrastructure minimizes travel times and costs for both passengers and freight, contributing to economic efficiency (Netirith & Ji, 2022). • Safety standards.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Efficiency. Well-designed infrastructure minimizes travel times and costs for both passengers and freight, contributing to economic efficiency (Netirith & Ji, 2022). • Safety standards.…”
Section: Resultsmentioning
confidence: 99%
“…• Integration. Effective transport infrastructure integrates different modes of transportation, allowing for smooth transfers and efficient movement of goods and people (Netirith & Ji, 2022). • Incorporation of technology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarania (2021) found that infrastructure construction can promote economic development by increasing the level of trade openness (Sarania 2021). Netirith and Ji (2022) pointed out that connectivity is important to link the community, regional integration, transportation and the direction of international trade import and export performance (Netirith and Ji 2022). Song (2021) found that railroads have a significant positive effect on the development of underdeveloped regions by connecting these regions with developed regions and bringing business opportunities (Song 2021).…”
Section: Theoretical Background Of Infrastructure Investment and The ...mentioning
confidence: 99%
“…A number of studies devoted to the analyses of efficiency of transport infrastructure have been carried out in the last decades. They consider the transport infrastructure connectivity using data envelopment analysis (DEA) [22]; review the regional development context [23] and influence on urban land use [24]; and evaluate railways and highways [25,26]. The theoretical background of the transport infrastructure development [27] and sustainable transportation aspects [28] are considered.…”
Section: Literature Reviewmentioning
confidence: 99%